2018
DOI: 10.1016/j.isci.2018.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Profiling Identifies Key Pathways Expressed by iPSCs Cultured in Different Commercial Media

Abstract: SummaryWe assessed the pluripotency of human induced pluripotent stem cells (iPSCs) maintained on an automated platform using StemFlex and TeSR-E8 media. Analysis of transcriptome of single cells revealed similar expression of core pluripotency genes, as well as genes associated with naive and primed states of pluripotency. Analysis of individual cells from four samples consisting of two different iPSC lines each grown in the two culture media revealed a shared subpopulation structure with three main subpopula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…Further evidence has also demonstrated that OCT3/4 downregulates the downstream gene expression of NANOG, SPP1/ OPN, SOX2, FBXO15, OTX2, and ZFP42/REX1 (Matoba, Niwa et al, 2006). The expression levels of NANOG, ZFP42 and c-MYC in our study were approximately 50 times lower than that of OCT3/4, which is consistent with previous results from sc-RNA-seq iPSC dataset (Daniszewski, Nguyen et al, 2018, Nguyen, Lukowski et al, 2018. Interestingly, NCRM1 and KYOU-DXR0109B, two commercial control lines with high passage number (>30 passages), express relatively high level of NANOG, SOX2 and ZFP42 and reduced levels of OCT3/4, suggesting that extended passaging enhances pluripotency gene expression (Koehler, Tropel et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Further evidence has also demonstrated that OCT3/4 downregulates the downstream gene expression of NANOG, SPP1/ OPN, SOX2, FBXO15, OTX2, and ZFP42/REX1 (Matoba, Niwa et al, 2006). The expression levels of NANOG, ZFP42 and c-MYC in our study were approximately 50 times lower than that of OCT3/4, which is consistent with previous results from sc-RNA-seq iPSC dataset (Daniszewski, Nguyen et al, 2018, Nguyen, Lukowski et al, 2018. Interestingly, NCRM1 and KYOU-DXR0109B, two commercial control lines with high passage number (>30 passages), express relatively high level of NANOG, SOX2 and ZFP42 and reduced levels of OCT3/4, suggesting that extended passaging enhances pluripotency gene expression (Koehler, Tropel et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Other studies also report on pluripotency levels of hPSCs in both feeder and feeder-free conditions and observed similar variations in these markers (Carpenter et al 2004;Ghasemi-Dehkordi et al 2015). StemFlex medium has been previously established as an efficient medium for routine culture, comparable to alternative media such as TeSR-E8, in which cells maintain expression of pluripotency markers and characteristic morphology (Daniszewski et al 2018).…”
Section: E8 Direct Protocolmentioning
confidence: 65%
“…This work provides a benchmark for high capacity sequencing platforms applied to highthroughput single cell RNA-seq libraries. iPSC -Consisted of undifferentiated human induced pluripotent stem cells (iPSCs) maintained with StemFlex (ThermoFisher Scientific) that were derived from two unrelated individuals (14).…”
Section: Discussionmentioning
confidence: 99%
“…Additional analyses were conducted on the iPSC and TMWC samples to evaluate the influence of sequencing platform on properties specific to these experiments. Using genotype 310 information from that was generated as described in (14), SNPs were called from the iPSC sample using demuxlet (12). To account for the downsampling of read depth in the MGISEQ-2000 data, only alignments from UMIs detected in the downsampled data were used.…”
Section: Bioinformatic and Computational Analysismentioning
confidence: 99%